Length-weight relations and condition factor of roach Rutilus rutilus (Linnaeus, 1758) in Lake Volvi (Northern Greece) - Kyritsi, Stavroula (Array, 2019)
Length-weight relations (LWRs) and different indices of condition factor for roach from Lake Volvi (Northern Greece) were estimated. Results showed that roach are heavier of a given length in Lake Volvi than in other areas worldwide, with females exhibited higher weight than males of the same length. Significant differences (P<0.05) of LWRs were also exhibited between sexes depending on month. CLARK condition factor peaked at the end of summer displaying no significant difference between sexes, whereas the other three estimated condition factors (Allometric, FULTON, LE CREN) peaked in winter. The estimation of different proxies of condition factor disaggregated by sex might reduce the uncertainty raised by the estimation of fish growth.